The control handbook (CRC, 1995)
The book is organized in three major sections, Fundamentals, Advanced Methods, and Applications. The Fundamentals are just what the name implicies, the basics of control engineering, including major subsections on digital control modeling of dynamical systems. The section on Advanced Methods consists of chapters dealing with more difficult and more specialized control problems, containing subsections devoted to the analysis and design of multiple-input multiple-output systems, adaptive control, nonlinear control, stochastic control, and the control of distributed parameter systems. The Applications section is included for several reasons. First, these chapters illustrate the diversity of control systems. Second, they provide examples of how the theory can be applied to specific practical proiblems. Third, they contain important information about aspects of control that are not fully captured by the theory, such as techniques for protecting against controller failure and the role of cost and complexity in specifying controller designs